DIAGNOSIS OF WATER QUALITY AND HEMEROBY ON THE TIETE RIVER IN MOGI DAS CRUZES - SP - Hitaka Soares, Jessica Akemi [UNESP]; Silva, Fabio Leandro da; Oliveira-Andreoli, Erica Zanardo; Fushita, Angela Terumi; Cunha-Santino, Marcela Bianchessi da; Bianchini Junior, Irineu (Univ Estadual Paulista Julio Mesquita Filho, 2023)
Increasing anthropised areas have an impact upon natural ecosystems, especially aquatic ones. Hence there is a need to investigate these impacts, a situation favoured through the application of indicators providing the foundations for decision-making. The present study has used the Water Quality Index (WQI), the Index of Trophic State (IET) and hemeroby to obtain a diagnosis of the waters of the Tiete River and of the land uses in the municipality of Mogi das Cruzes-SP, inserted in the Alto Tiete, Baixada Santista and Paraiba do Sul Water Management Units. There have been two sampling campaigns in the Tiete River between 2015 and 2016. Land use and cover typologies have been identified by visual interpretation from a satellite image, which enabled the identification of the degrees of hemeroby. The results have shown that the water quality loss of the Tiete River relates to improper dumping of household effluents and diffuse pollution. The main land cover typologies for 2016 are the following: (i) Native Vegetation, (ii) Urbanized Area and (iii) Grassland. Despite the fact that the landscape is composed by low hemeroby ecotopes (Native Vegetation), the Urbanized Area with the highest degree of hemeroby has been responsible for the changes in water quality found in the Tiete River. Results favour the establishment of strategies to minimize adverse impacts on ecosystems and supports to the decision-making process.
Keywords: Aquatic Ecology; Naturalness; Environmental Management; Landscape Ecology; Tiete River